A Framework for Measuring the Progress in Exoskeleton Skills in People with Complete Spinal Cord Injury - van Dijsseldonk, Rosanne B.; Rijken, Hennie; van Nes, Ilse J. W.; van de Meent, Henk; Keijsers, Noel L. W. (Frontiers in Neuroscience, 2017)
For safe application of exoskeletons in people with spinal cord injury (SCI) at home or in the community, it is required to have completed an exoskeleton training in which users learn to perform basic and advanced skills. So far, a framework to test exoskeleton skills is lacking. The aim of this study was to develop and test the hierarchy and reliability of a framework for measuring the progress in the ability to perform basic and advanced skills. Twelve participants with paraplegia were given twenty-four training sessions in eight weeks with the Rewalk-exoskeleton. During the 2nd, 4th and 6th training week the Intermediate-skills-test was performed consisting of twenty-seven skills, measured in an hierarchical order of difficulty, until two skills were not achieved. When participants could walk independently, the Final-skills-test, consisting of twenty skills, was performed in the last training session. Each skill was performed at least two times with a maximum of three attempts. As a reliability measure the consistency was used, which was the number of skills performed the same in the first two attempts relative to the total number. Ten participants completed the training program. Their number of achieved intermediate skills was significantly different between the measurements XF2(2)=12.36, p=.001. Post hoc analysis revealed a significant increase in the median achieved intermediate skills from 4 [1–7] at the first to 10.5 [5–26] at the third Intermediate-skills-test. The rate of participants who achieved the intermediate skills decreased and the coefficient of reproducibility was 0.98. Eight participants met the criteria to perform the Final-skills-test. Their median number of successfully performed final skills was 16.5 [13–20] and 17 [14–19] skills in the first and second time. The overall consistency of >70% was achieved in the Intermediate-skills-test (73%) and the Final-skills-test (81%). Eight out of twelve participants experienced skin damage during the training, in four participants this resulted in missed training sessions. The framework proposed in this study measured the progress in performing basic and advanced exoskeleton skills during a training program. The hierarchical ordered skills-test could discriminate across participants’ skill-level and the overall consistency was considered acceptable.